Natural resources, social space and livelihood strategies in land reform settlements in the Brazilian Amazon (Southeast of Pará) - Karin Marita Naase (Boletim do Museu Paraense Emílio Goeldi. Ciências Humanas, 2010)
Nearly 38% of all families living in settlements of Brazilian land reform are in the Amazon. One of the problems is that large segments of the settlers do not fit into the target group of land reform and more than 50% of the allotments conceded by land reform already have been commercialized by the settlers – even before receiving the final land title. This paper is based upon field research carried on in the southeast of State of Pará with the intention of analyzing the livelihood strategies of land reform settlers and relationship between these settlers and their habitat (Settlement Project), understood as social space and space of natural resources. The guiding questions of this inquiry are: which are the settlers’ livelihood strategies? Are they sustainable? Which are the reasons of the settlers to leave the hamlet and commercialize their allotments? How is their relationship to the natural and social environment of the settlement? How do public policies interfere? Issues related to public goods and self-governed common-pool resources are very important to these questions. The social organization of the settlers, as well as the institutional guaranties given by the State are therefore the central axis of this article.